Cities and places. Sixth part - Soltan, Frederic; Rabotteau, Dominique ([New Hampshire] : Chip Taylor Communications, 2007)
This an epic collection of very special encounters with Indian culture across the entire subcontinent. This series take the viewer to four cities/places. Focusing on specific individuals and families at each location, describing their situation and adding a human touch to the visual element
DVD format
Keywords: India -- Social life and customs; India -- History